Invasive cutaneous mucormycosis in a preterm neonate presenting as a vesicobullous lesion - Shashank Mishra; Divya Shelly; Divya Gupta; Reena Bharadwaj (Wolters Kluwer Medknow Publications, 2018)
Mucormycosis is a relatively rare fungal infection seen in immunocompromised patients. Very few cases of invasive cutaneous mucormycosis occurring in neonates have been reported in literature. It is an aggressive disease with a mortality rate of around 64% in neonates, so a high index of suspicion is essential for rapid diagnosis and definitive treatment with broad-spectrum antifungals such as Amphotericin B. We present a case of a premature infant born at 25 weeks of gestation who developed vesicobullous lesions all over the body on day 5 of life. Biopsy from the vesicles confirmed the presence of angioinvasive fungal hyphae of mucormycosis which were highlighted on Periodic acid-Schiff and Grocott stain.